Investigation on the interaction between myricetin and dihydromyricetin with trypsin, α‐chymotrypsin, lysozyme by spectroscopy and molecular docking methods. (29th March 2022) - Meng, Xianxin; Nan, Guanjun; Shi, Bowen; Li, Wanlu; Liu, Henglin; Lin, Rong; Yang, Guangde; Zheng, Shaohua
Abstract: The interaction between myricetin and dihydromyricetin with trypsin, α‐chymotrypsin and lysozyme was investigated using multispectral and molecular docking methods. The results of fluorescence quenching revealed that myricetin and dihydromyricetin could quench the intrinsic fluorescence of three different proteinases through a static quenching procedure. The binding constant and number of binding sites at different temperatures were measured. The thermodynamic parameters obtained at different temperatures showed van der Waals interactions and hydrogen bonds played the main roles in the interaction of myricetin with trypsin and lysozyme, hydrophobic force was dominant both in myricetin with α‐chymotrypsin interaction and dihydromyricetin with trypsin and lysozyme interaction, as for the electrostatic forces, it was mainly the driving force in dihydromyricetin binding to α‐chymotrypsin. There was non‐radiative energy transfer between three proteinases and myricetin or dihydromyricetin with high probability. The microenvironment of trypsin, α‐chymotrypsin and lysozyme is changed. The docking studies revealed that myricetin and dihydromyricetin entered the hydrophobic cavity of three proteinases and formed hydrogen bonds. The binding affinity of myricetin or dihydromyricetin is different with the trypsin, α‐chymotrypsin and lysozyme due to the different molecular structure. Abstract : The interaction between myricetin (MY) and dihydromyricetin (DMY) with trypsin, α‐chymotrypsin and lysozyme were investigated using multi spectroscopic and molecular docking methods.